Seeing Culture Through Space: How Visual and Spatial Arrangements Communicate Sasak Cultural Identity in Dusun Sade's Tourism Setting - Furqonita Pramadanti Wahyudi; Anang Sujoko; Desi Dwi Prianti (FAKULTAS DAKWAH UIN SALATIGA, 2026)
This study examines how cultural identity is communicated without words through the visual and spatial arrangements of Dusun Sade, a living Sasak heritage village in Lombok, Indonesia. Drawing on Foucault's conceptualization of spatial power and Rose's framework of the visual apparatus, the study argues that cultural identity communication in tourism operates through the systematic organization of space, movement, and visibility rather than through explicit narration or display. Systematic photo-documentation yielded a corpus of 127 images collected during fieldwork in December 2025, analyzed for recurring spatial and visual patterns at both empirical and discursive levels. Three patterns were identified: concentrated visitor movement along a primary corridor, consistent architectural emphasis on natural materials within that corridor, and the exclusive positioning of cultural and commercial activities along the established visitor route. Together, these arrangements produce a selective but coherent visual representation of the Sasak tradition that visitors encounter as natural and authentic. This study extends existing applications of Foucauldian and Rose's frameworks to the context of inhabited traditional villages, demonstrating that spatial governance operates as a mechanism of cultural identity production in living heritage tourism settings.